Nuclear retention of the lncRNA SNHG1 by doxorubicin attenuates hnRNPC–p53 protein interactions. (6th March 2017) - Shen, Yuan; Liu, Shanshan; Fan, Jiao; Jin, Yinghua; Tian, Baolei; Zheng, Xiaofei; Fu, Hanjiang
Abstract: The protein p53 plays a crucial role in the regulation of cellular responses to diverse stresses. Thus, a major priority in cell biology is to define the mechanisms that regulate p53 activity in response to stresses or maintain it at basal levels under normal conditions. Moreover, further investigation is required to establish whether RNA participates in regulating p53's interaction with other proteins. Here, by conducting systematic experiments, we discovered a p53 interactor—hnRNPC—that directly binds to p53, destabilizes it, and prevents its activation under normal conditions. Upon doxorubicin treatment, the lncRNA SNHG1 is retained in the nucleus through its binding with nucleolin and it competes with p53 for hnRNPC binding, which upregulates p53 levels and promotes p53‐dependent apoptosis by impairing hnRNPC regulation of p53 activity. Our results indicate that a balance between lncRNA SNHG1 and hnRNPC regulates p53 activity and p53‐dependent apoptosis upon doxorubicin treatment, and further indicate that a change in lncRNA subcellular localization under specific circumstances is biologically significant. Synopsis: p53 is a crucial regulator of cellular responses to toxic stress. This study identifies hnRNPC as a destabilizing p53 regulator. Doxorubicin treatment induces the nuclear retention and subsequent interaction of the lncRNA SNHG1 with hnRNPC, which impairs p53 destabilization. The ribonucleoprotein hnRNPC directly binds to p53. The hnRNPC interaction destabilizes p53 and prevents its activation. Doxorubicin treatment retains the lncRNA SNHG1 in the nucleus through its binding with nucleolin. Nuclear SNHG1 traps hnRNPC, which stabilizes p53 and promotes p53‐dependent apoptosis. Abstract : p53 is a crucial regulator of cellular responses to toxic stress. This study identifies hnRNPC as a destabilizing p53 regulator. Doxorubicin treatment induces the nuclear retention and subsequent interaction of the lncRNA SNHG1 with hnRNPC, which impairs p53 destabilization.